2019
DOI: 10.1101/736686
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

p62-DNA-encoding plasmid reverts tumor grade, changes tumor stroma, and enhances anticancer immunity

Abstract: Previously, we reported that the administration of a p62/SQSTM1-encoding plasmid demonstrates high safety and clinical benefits for human cancer patients, having also suppressed tumor growth and metastasis in dogs and mouse models. Here we investigated the mechanistic aspects of these effects. In mammary tumors bearing-dogs, p62 plasmid i.m. injections reduced tumor volumes, and reverted tumor grade to less aggressive lesions in 5 out of 6 animals, with one carcinoma switching to benign adenoma. The treatment … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 42 publications
(1 reference statement)
0
3
0
Order By: Relevance
“…In accordance, Yan et al have shown that overexpressed wild-type p62 in ovarian cancer cells significantly increased activation of caspase 8, with consequent apoptosis, and ameliorates the response to cisplatin [ 20 ]. Moreover, evidence has been provided that p62 ectopic expression in vivo reverts tumor grade, changes tumor stroma and enhances anticancer immunity [ 87 ]. Even more recently, Choi et al showed increased levels of nuclear p62 upon ascorbic acid treatment in breast cancer cells correlated with endoplasmic reticulum stress and cell death [ 88 ].…”
Section: Oncojanus Role Of P62mentioning
confidence: 99%
“…In accordance, Yan et al have shown that overexpressed wild-type p62 in ovarian cancer cells significantly increased activation of caspase 8, with consequent apoptosis, and ameliorates the response to cisplatin [ 20 ]. Moreover, evidence has been provided that p62 ectopic expression in vivo reverts tumor grade, changes tumor stroma and enhances anticancer immunity [ 87 ]. Even more recently, Choi et al showed increased levels of nuclear p62 upon ascorbic acid treatment in breast cancer cells correlated with endoplasmic reticulum stress and cell death [ 88 ].…”
Section: Oncojanus Role Of P62mentioning
confidence: 99%
“…Recently, the p62 plasmid was reported to act as a promising anticancer agent in rodent laboratory models (F. Venanzi et al, 2013), spontaneous cancers in dogs and cats (Gabai et al, 2014 and unpublished data), and in humans (Ponomarenko et al, 2017, 2020). The plasmid remodels a tumor microenvironment making it more favorable for anticancer treatments (F. M. Venanzi et al, 2019). The p62 plasmid can also partially restore both metabolic and behavioral components of high‐calorie, diet‐induced obesity (Halenova et al, 2017), partially prevent age‐related macular degeneration (Kolosova et al, 2018), and cause bone and bone marrow “rejuvenation” (Agas & Sabbieti, 2021; Agas et al, 2020; Lacava et al, 2019; Sabbieti et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The plasmid remodels a tumor microenvironment making it more favorable for anticancer treatments (F. M. Venanzi et al, 2019). The p62 plasmid can also partially restore both metabolic and behavioral components of high-calorie, diet-induced obesity (Halenova et al, 2017), partially prevent age-related macular degeneration (Kolosova et al, 2018), and cause bone and bone marrow "rejuvenation" (Agas & Sabbieti, 2021;Agas et al, 2020;Lacava et al, 2019;Sabbieti et al, 2015).…”
Section: Discussionmentioning
confidence: 99%